2018
DOI: 10.5194/acp-18-7489-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of biogenic and anthropogenic emissions on summertime ozone formation in the Guanzhong Basin, China

Abstract: Abstract. This study is the first attempt to understand the synergistic impact of anthropogenic and biogenic emissions on summertime ozone (O3) formation in the Guanzhong (GZ) Basin where Xi'an, the oldest and the most populous city (with a population of 9 million) in northwestern China, is located. Month-long (August 2011) WRF-Chem simulations with different sensitivity experiments were conducted and compared with near-surface measurements. Biogenic volatile organic compounds (VOCs) concentrations was charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 73 publications
5
32
0
Order By: Relevance
“…The estimated contribution of sources outside China declines to 46 % in summer, which agrees well with the 47 % value inferred from Nagashima et al (2010). Li et al (2012) applied the OSAT tool in the CAMx to apportion O 3 sources in South China, and they reported that superregional sources contributed 55 % and 71 % of monthly mean O 3 in summer and autumn, respectively. They also pointed out that regional and local sources play more important roles in O 3 pollution episodes (Li et al, 2002).…”
Section: O 3 Contribution From Individual Source Regionssupporting
confidence: 76%
See 1 more Smart Citation
“…The estimated contribution of sources outside China declines to 46 % in summer, which agrees well with the 47 % value inferred from Nagashima et al (2010). Li et al (2012) applied the OSAT tool in the CAMx to apportion O 3 sources in South China, and they reported that superregional sources contributed 55 % and 71 % of monthly mean O 3 in summer and autumn, respectively. They also pointed out that regional and local sources play more important roles in O 3 pollution episodes (Li et al, 2002).…”
Section: O 3 Contribution From Individual Source Regionssupporting
confidence: 76%
“…Strong but distinctive seasonal variations in O 3 observed in India and China have been linked to higher emissions of precursor gases (Lal et al, 2000) and summer monsoons (Kumar et al, 2010;Lu et al, 2018b;Wang et al, 2017). The contributions of individual economic sectors and source regions were reported based on sensitivity simulations and source apportionment techniques (Gao et al, 2016a;Li et al, , 2016Li et al, , 2012Lu et al, 2019;Wang et al, 2019). With respect to the enhanced concentrations of O 3 over the past years, Sun et al (2019) attributed them to elevated emissions of anthropogenic volatile organic compounds (VOCs), while Li et al (2019) argued that an inhibited aerosol sink for hydroperoxyl radicals induced by decreased PM 2.5 over 2013-2017 played a more important role in the North China Plain (NCP).…”
Section: Introductionmentioning
confidence: 99%
“…NOx/VOC emission would correspondingly promote the formation of ozone (Tang et al, 2010;Li et al, 2018;Li et al, 2019). Both AVOC and BVOC show the increasing trend since 2010, as shown in Figure 6, with an increase of 9.7% for AVOC and 34.6% for BVOC from 2010 to 2016, respectively.…”
Section: Comparison Of Bvoc Emission With Anthropogenic Emission In Cmentioning
confidence: 98%
“…The estimated increase of BVOC in regions like the Qinling Mountains and southern China are expected to affect regional air quality. For the Qinling Mountains and surrounding areas, as estimated by Li et al (2018) using the WRF-chem model, the average contribution of BVOC to O3 could reach 16.8 ppb for the https://doi.org /10.5194/acp-2020-28 Preprint. Discussion started: 16 March 2020 c Author(s) 2020.…”
Section: The Regional Variability Of Bvoc Emission In Chinamentioning
confidence: 99%
See 1 more Smart Citation